2014
DOI: 10.2174/1574886309666140211113635
|View full text |Cite
|
Sign up to set email alerts
|

Renal Injury Following Intravitreal Anti-VEGF Administration in Diabetic Patients with Proliferative Diabetic Retinopathy and Chronic Kidney Disease - A Possible Side Effect?

Abstract: The use of intravitreal injections of anti-Vascular Endothelial Growth Factor (anti-VEGF) has been used for a broad spectrum of ocular pathologic entities. Although the dose of anti-VEGF agents used for treating eye disease is minute compared with that used intravenously, intraocular administration can lead to systemic absorption and reduce serum VEGF levels. Several systemic side effects, such as hypertension and cardiovascular complications have been rarely reported in the literature. Renal complications of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 0 publications
0
29
2
2
Order By: Relevance
“…The doses of the intravitreously administered VEGF inhibitors in the present study were much lower than those administered intravenously 13 ; however, aflibercept and ranibizumab could be detected in the glomerular capillaries in monkeys after one intravitreal injection 14 . In addition, a few cases of AKI events after intravitreal anti-VEGF therapy have been reported, although we were unable to explain the differences observed between the current study and the AKI cases 7,8 . Therefore, monitoring of renal function should be recommended, even in patients receiving intravitreal anti-VEGF therapy.…”
Section: Discussioncontrasting
confidence: 78%
“…The doses of the intravitreously administered VEGF inhibitors in the present study were much lower than those administered intravenously 13 ; however, aflibercept and ranibizumab could be detected in the glomerular capillaries in monkeys after one intravitreal injection 14 . In addition, a few cases of AKI events after intravitreal anti-VEGF therapy have been reported, although we were unable to explain the differences observed between the current study and the AKI cases 7,8 . Therefore, monitoring of renal function should be recommended, even in patients receiving intravitreal anti-VEGF therapy.…”
Section: Discussioncontrasting
confidence: 78%
“…This confirmed primate studies that detected anti-VEGF agents in glomeruli one day after intravitreal injection (74). Furthermore, glomerular dysfunction has been reported for all intravitreal VEGF antagonists currently used in patients (75, 76). Not all patients are affected, but preexisting renal pathology may increase susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 2 renal transplant patients were reported to have developed antibody-mediated rejection after intravitreal therapy for ARMD (75). Another study reported diabetic patients with nephropathy and retinopathy whose renal function deteriorated from stage IV to stage V chronic kidney disease after intravitreal anti-VEGF (76). Therefore, documentation of renal function, blood pressure, and urinalysis before and during treatment with anti-VEGF agents would be prudent, particularly in ARMD patients who have renal comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…38 Several studies in the nephrology literature have reported the presence of renal complications following intravitreal anti-VEGF therapy, including proteinuria and hypertension. [39][40][41] Tschulakow et al 27 found that aflibercept and ranibizumab were both detected within glomerular capillaries after a single intravitreal injection of these agents in a cynomolgus primate model. Their findings are consistent with the rapid accumulation of ranibizumab in the kidneys following intravitreal injection found in this investigation.…”
Section: Discussionmentioning
confidence: 99%